ANALISIS PERBANDINGAN BIAYA PETI KEMAS DENGAN METODE PREVENTIF MAINTENANCE DAN REPAIR POLICY PADA PT SAMUDERA LOGISTIK - Radna Ningsih; Ativa Rahmadani (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
Lack of maintenance costs for containers and inefficiency of container maintenance schedules, resulting in increased maintenance costs so as not to optimize the company's revenue. The purpose of this study is to determine the cost of container maintenance to be more efficient and effective based on preventive maintenance and repair policy. Data collection was obtained from interviews and primary data collection. Data analysis uses preventive maintenance and repair policy methods. The results showed that the most optimal treatment using preventive maintenance and repair policy methods in the crates was Rp. 75,648,918 and Rp. 73,537,274 for preventive maintenance, while for the repair policy, Rp. 226,390,336 of the results of preventive and repair costs. policy that has been processed. The maintenance schedule for containers is done in the 6th and 12th months by using preventive maintenance and repair policy methods for container maintenance costs to be lower.